Regulation of the Fas death pathway by FLICE-inhibitory protein in primary human B cells - Hennino, Ana; Krammer, Peter H. (The journal of immunology, 2000)
The Fas/Fas ligand (L) system plays an important role in the maintenance of peripheral B cell tolerance and the prevention of misguided T cell help. CD40-derived signals are required to induce Fas expression on virgin B cells and to promote their susceptibility to Fas-mediated apoptosis. In the current study, we have analyzed the early biochemical events occurring upon Fas ligation in CD40L-activated primary human tonsillar B cells with respect to Fas-associated death domain protein (FADD), caspase-8/FADD-like IL-1β-converting enzyme (FLICE), and c-FLICE inhibitory protein (FLIP). We report here that Fas-induced apoptosis in B cells does not require integrity of the mitochondrial Apaf-1 pathway and that caspase-8 is activated by association with the death-inducing signaling complex (DISC), i.e., upstream of the mitochondria. We show that both FADD and the zymogen form of caspase-8 are constitutively expressed at high levels in virgin B cells, whereas c-FLIP expression is marginal. In contrast, c-FLIP, but neither FADD nor procaspase-8, is strongly up-regulated upon ligation of CD40 or the B cell receptor on virgin B cells. Finally, we have found that c-FLIP is also recruited and cleaved at the level of the DISC in CD40L-activated virgin B cells. We propose that c-FLIP expression delays the onset of apoptosis in Fas-sensitive B cells. The transient protection afforded by c-FLIP could offer an ultimate safeguard mechanism against inappropriate cell death or allow recruitment of phagocytes to ensure efficient removal of apoptotic cells.